(untitled) (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2022)
The increasing need for energy cannot be separated from the increasing population, increasing people’s living standards, increasing number of vehicles, industrial growth which is increasing very rapidly, causing increased energy consumption. However, the government through the National Energy Policy (KEN) issued several solutions to overcome these problems, namely by converting and intensifying energy. This study aims to determine the effectiveness of hydrogen generators in producing hydrogen gas against people’s dependence on conventional energy or LPG gas. In the context of this writing, the authors chose research on Jl. Soekarno Hatta KM 3.5 RT :038 No: 65 Batu Ampar. This study uses research methods with observation, systematic recording directly on the object, as well as taking photos and taking data from other reference sources related to the problem. Based on the research that researchers have done regarding the production of hydrogen gas with an electrolysis-based hydrogen generator, it can be concluded that if the tool that the researcher makes is not effective in overcoming people’s dependence on the use of conventional energy or LPG, the cost required to produce 3 kg of hydrogen gas with this tool is IDR 428. 504,141, while the price of 3 kg LPG gas is IDR 25,000